Lean maternal hyperglycemia alters offspring lipid metabolism and susceptibility to diet-induced obesity in mice†. Issue 5 (29th January 2019) - Talton, Omonseigho O; Bates, Keenan; Salazar, Shirley Rojas; Ji, Tieming; Schulz, Laura Clamon
Abstract: We previously developed a model of gestational diabetes mellitus (GDM) in which dams exhibit glucose intolerance, insulin resistance, and reduced insulin response to glucose challenge only during pregnancy, without accompanying obesity. Here, we aimed to determine how lean gestational glucose intolerance affects offspring risk of metabolic dysfunction. One cohort of offspring was sacrificed at 19 weeks, and one at 31 weeks, with half of the second cohort placed on a high-fat, high-sucrose diet (HFHS) at 23 weeks. Exposure to maternal glucose intolerance increased weights of HFHS-fed offspring. Chow-fed offspring of GDM dams exhibited higher body fat percentages at 4, 12, and 20 weeks of age. At 28 weeks, offspring of GDM dams fed the HFHS but not the chow diet (CD) also had higher body fat percentages than offspring of controls (CON). Exposure to GDM increased the respiratory quotient (Vol CO2 /Vol O2 ) in offspring. Maternal GDM increased adipose mRNA levels of peroxisome proliferator-activated receptor gamma ( Pparg ) and adiponectin ( Adipoq ) in 31-week-old CD-fed male offspring, and increased mRNA levels of insulin receptor ( Insr ) and lipoprotein lipase ( Lpl ) in 31-week-old male offspring on both diets. In liver at 31 weeks, mRNA levels of peroxisome proliferator-activated receptor alpha ( Ppara ) were elevated in CD-fed male offspring of GDM dams, and male offspring of GDM dams exhibited higher mRNA levels of Insr on both diets. Neither fasting insulin nor glucose tolerance was affected by exposure to GDM. Our findings show that GDM comprising glucose intolerance only during pregnancy programs increased adiposity in offspring, and suggests increased insulin sensitivity of subcutaneous adipose tissue. Abstract : Glucose intolerance in a lean model of GDM results in offspring with increased lipid storage mediated by insulin sensitive adipose tissue and decreased lipid energy utilization.